Whey proteins. Overview of clinical trials - Sukkar, S.G.; Iorio, E.L. (Progress in Nutrition, 2011)
SummaryWhey proteins, due to their documented biological properties that are exerted by their complex or due to the singular characteristics of their single fractions, have been and continue to be used with success in numerous pathological (e.g. metabolic, cardiovascular, degenerative and infective disorders etc.) and physiological conditions (e.g. sports activities). The purpose of this second section is in fact the presentation of a series of experimental and clinical studies carried out both on animals and in humans, in which the efficacy of whey protein formulations was evaluated in comparison to certain outcomes. Despite what has been done to date, further studies are needed in order to identify a more defined role - in terms of type, dose, administration modality, and pharmacokinetics etc. – of whey proteins in nutritional supplementation or, more precisely, as nutraceutics, especially in pathological situations, in association or in synergy with conventional medical or surgical treatments. Please note that in this section were not taken into account the clinical applications of whey proteins, respectively, in oncology, in asthenic syndrome of autoimmune diseases, in neurology and in cystic fibrosis  at which is dedicated the Section III of this issue.Le proteine da siero di latte. Rassegna di studi cliniciRiassuntoLe proteine da siero di latte, grazie alle documentate proprietà biologiche esibite nel loro complesso o in virtù delle singolari caratteristiche di singole frazioni, sono state e continuano ad essere impiegate con successo in svariate condizioni sia patologiche (es. malattie metaboliche, cardiovascolari, degenerative, infettive ecc.) sia fisiologiche (es. attività sportiva). Scopo di questa seconda sezione è, appunto, la presentazione di una rassegna di studi sperimentali e clinici, condotti sia in modelli animali che sull’uomo, nei quali è stata valutata l’efficacia di formulazioni di proteine da siero di latte rispetto a determinati out come. Molto è stato fatto ma molto resta ancora da fare per l’individuazione di un ruolo sempre più definito – in termini di tipologia, dosaggio, modalità di somministrazione, farmacocinetica ecc. – delle proteine da siero di latte come integratori nutrizionali o, meglio, come nutraceutici, specialmente in situazioni patologiche, in associazione o in sinergia con i trattamenti medici o chirurgici convenzionali. Precisiamo che in questa sezione non sono state prese in considerazione le applicazioni cliniche delle sieroproteine da latte rispettivamente in oncologia, nella sindrome da astenia da patologie autoimmuni, in neurologia e nella fibrosi cistica in quanto ad esse è dedicata la sezione III del fascicolo.